2019
DOI: 10.3366/cor.2019.0169
|View full text |Cite
|
Sign up to set email alerts
|

Towards a decade of synergising corpus linguistics and critical discourse analysis: a meta-analysis

Abstract: The incorporation of corpus linguistics (CL) methods within critical discourse analysis (CDA) has increasingly gathered momentum over the last decade. This paper surveys studies using this triangulated framework, drawing on a database of 121 studies collected from three citation indexes: Social Sciences Citation Index, Arts and Humanities Citation Index, and Scopus. It presents a meta-analysis of these studies focussing on four variables, namely their chronological development, the domains of engagement, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…A synthesis of purposively selected 39 studies conducted by a range of researchers, both faculty and students, on the language of evaluation in academic writing in Ghana was undertaken, by way of addressing the key linguistic, pragmatic, and rhetorical features. Content analysis (or thematic analysis), inclusion/exclusion, and comparative approaches were adopted in line with Nartey and Mwinlaaru (2019).…”
Section: Discussionmentioning
confidence: 99%
“…A synthesis of purposively selected 39 studies conducted by a range of researchers, both faculty and students, on the language of evaluation in academic writing in Ghana was undertaken, by way of addressing the key linguistic, pragmatic, and rhetorical features. Content analysis (or thematic analysis), inclusion/exclusion, and comparative approaches were adopted in line with Nartey and Mwinlaaru (2019).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the benefit of complementing a DA with a corpus or vice versa lies in the conjunction of quantitative and qualitative methods (Knoblock, 2020). A meta-analysis by Nartey and Mwinlaaru (2019) has shown that corpus-assisted approaches are frequently used in linguistics, and yet they identify a lack of such research "in the allied field of critical genre analysis and forensic contexts as well (as) those of contrastive/intercultural rhetoric, narrative inquiry/analysis, mediated discourse analysis, and conversation analysis have hardly been engaged" (p. 19, my emphasis). Thus, the present paper aims at contributing to the extant literature in the area of corpus-assisted discourse analysis in forensic contexts (e.g., Coulthard, 1994;Kredens, 2002;Cotterill, 2003;Heffer, 2005;Gruber, 2014;Felton Rosulek, 2015;Gales, 2015;Tkacuková, 2015;Wright, 2021), and it is also the first one, to my knowledge, to address the language of private prison corporations in the United States.…”
Section: Data Methodology and Research Questionsmentioning
confidence: 99%
“…Where needed, computer assisted discourse analysis of the texts was used, especially when adopting and extending the corpus assisted multimodal discourse analysis (CAMDA) framework proposed by Bednarek and Caple (2014, 2017). The use of corpus assisted analysis has been shown to be effective in complementing findings of smaller data sets (generated by CDA or discourse analysis), by triangulating findings within a larger data set (see Baker et al, 2008; also Nartey & Mwinlaaru, 2019). Details of this process are laid out in the analytical approach section.…”
Section: Critical Discourse Analysis With Corpus Linguisticsmentioning
confidence: 99%